Implementación de un algoritmo de identificación de bloques de sintenia a partir de alineamientos en ngsep (2020)
Synteny blocks are sets of similar regions between genomes or within the same genome. The identification of these blocks allows for genomic evolution studies. Recent work in comparative genomics demonstrates an interest in having synteny blocks identification tools that are easy to use and to integrate into existing workflows. Despite the fact that there are currently various tools for identifying synteny blocks, their integration into workflows is difficult. Taking this into account, this functionality was implemented in the NGSEP software. For this, different tools currently used in the identification of synteny blocks were explored and the HalSynteny algorithm was selected and implemented in NGSEP. This algorithm consists of constructing a directed acyclic graph based on the alignments and, based on these, find the synteny blocks using as parameters the distance between the alignments and the total length of the aligned regions that make up a synthesis block. The execution times of both tools were compared and a sensitivity and specificity analysis was performed. The implementation in NGSEP has a much shorter execution time and achieves higher sensitivity in tests compared to HalSynteny. Both tools maintain a similar specificity between them when they are at their maximum sensitivity.